Compositional features of Manchukuo architecture - Антон А. Ким; Екатерина Пугачева (Проект Байкал)
The study examines the Japanese period of architecture development in Northeast China (Manchuria), which represents a separate branch of Japanese colonial architecture. To determine the patterns of development of compositional techniques, the period is divided into two stages (1932–1938 and 1938–1945), and the main patterns of spatial composition are revealed, including methods of proportionation based on module 1 to 2. The article determines stylistic preferences, which, as the architecture of Manchukuo developed, transformed from neoclassicism to Art Deco and modernism. It was revealed that despite the changes in style, the principles of building a three-dimensional composition remained unchanged.